Acid reflux into the oesophagus does not influence exercise-induced airway narrowing in bronchial asthma. Issue 10 (1st June 2007) - Ferrari, M; Bonella, F; Benini, L; Ferrari, P; De Iorio, F; Testi, R; Lo Cascio, V
Abstract : Objectives: A few studies on small patient series have investigated the relationship between gastroesophageal reflux and bronchial responsiveness as expressed by exercise-induced bronchoconstriction (EIB), with non-conclusive results. The aim of this study was to evaluate whether the presence of acid in the oesophagus may influence EIB. Methods: 45 patients with bronchial asthma underwent spirometry, exercise challenge on bicycle ergometer and 24 h oesophageal pH monitoring. Subjects with EIB (Forced expiratory volume in the first second (FEV1)) percentage decrease after exercise (ΔFEV1) ⩾15%, n = 28) were retested after a 2 week treatment course with omeprazole 40 mg/daily. Exercise at baseline was performed at the same time as oesophageal pH monitoring. Results: In basal condition, there was no difference in FEV1, acid exposure time or number of refluxes measured during 24 h pH monitoring between patients with and without EIB. There was no relationship between spirometry results and ΔFEV1 on one hand, and parameters of gastroesophageal reflux on the other. Nine patients with EIB (31.0%) and six patients without EIB (37.5%) had one or more episodes of GER during exercise challenge, without significant differences between the two groups. After gastric acid inhibition by omeprazole, ΔFEV1 did not change significantly. Conclusions: The results indicate that acid in the oesophagus, or its short-term inhibition by proton pump inhibitors, has no influence on exercise-induced bronchoconstriction.